Pelaksanaan Employer Branding PT. Arya Noble - Zahra Alifia; Hanny Hafiar; Anwar Sani (Communication, 2020)
This research entitled “The Implementation of Employer Branding by PT. Arya Noble” is a descriptive study with qualitative data that focuses on knowing the employer branding process carried out by PT. Arya Noble in forming the image “to be an excitement place to grow and creating values”. This study aims to discover how is (1) the employer value proposition is developed by PT. Arya Noble, (2) the external marketing stage of the employer brand conducted by PT. Arya Noble, (3) the internal marketing stage of the employer brand conducted by PT. Arya Noble. This research used positivism paradigm with descriptive qialitative methode. Data collection techniques used include moderate participative observation, in-depth interviews, and literature study. The data validity technique uses source triangulation. The results of this research revealed that (1) The EVP by PT. Arya Noble consist company culture “The Now Values” as a basic guideline for employees to behave, the use of Top-Down management style to increase performance, the use of OKRS system in performance appraisal, as well as consumer impression on the Sub-Business Unit, (2) The external marketing stage is carried out by using online and offline tools to form attractions and build awareness to the public, both for those who were looking for a job or not. So they would understand and join the company, (3) The internal marketing stage is carried out through training activities, rewards, and internalisation of “The Now Values” culture to the employees in order to improve the performance as well as employees psychological contract towards the company. The conclusion is company has done all of the employer branding process. However there are shortcomings that need to be overcome on every step like employment image, gamification and career tab on website, advertising campaign, and also the application for company culture.